Assessing the reliability of open-source data used for spatial characterisation of urban sanitation infrastructure—a field study in Rajshahi, Bangladesh - Sultana, Mst Sufia; Waine, Toby W.; Bari, Niamul; Tyrrel, Sean F. (Springer, 2025)
Urban sanitation in rapidly growing secondary cities remains a critical challenge, particularly in unsewered areas. This study evaluates the effectiveness of open-source data for modelling the sources and movement of faecal matter in such contexts, with a specific focus on Rajshahi, an unsewered secondary city in Bangladesh. By triangulating data from direct observations, key informant interviews (KIIs), and focus group discussions (FGDs), we assess the reliability of using open-source data to map faecal matter flow. The findings demonstrate an 80% alignment between the model’s simulated flow directions and actual field observations, highlighting the potential of using open-source data in urban sanitation management. Furthermore, the study reveals that 80% of buildings are connected to storm drains with many allowing faecal matter to overflow from septic tanks, thus posing a health risk. Despite efforts by the City Corporation to manage the drainage system through reactive measures like drain scraping and unblocking, blocked and overflowing drains remain prevalent, particularly during the rainy season. KIIs and (FGDs) highlight a lack of proactive maintenance and widespread unawareness of sanitation management systems. This integration of field-based insights with open-source data supports for a more proactive, data-driven approach to urban sanitation management in secondary cities, ultimately aiming to enhance public health and quality of life.
Keywords: Faecal matter; Fieldwork; Open-source data; Rajshahi, Bangladesh; Sanitation infrastructure; Urban sanitation; Environmental Sciences